Pavement Condition Evaluation and Its Relationship with Traffic Loading on Kenanga Road Segment - Ahmad Rafii (International Journal of Natural Science Studies and Development (IJOSS), 2026)
Kenanga Road in the City of Padangsidimpuan is a primary collector road that functions as a convergence point for traffic flows heading toward the city's Central Business District. A previous traffic engineering study on this segment identified a Volume-to-Capacity (V/C) ratio of 0.68 with an average speed of 24.50 km/h, but did not evaluate the physical and structural condition of the pavement as a factor influencing road performance. This study aims to evaluate pavement condition using the Pavement Condition Index (PCI) and International Roughness Index (IRI) across ten segments spanning 1,000 meters, and to analyze their relationship with cumulative traffic loading expressed as Equivalent Single Axle Load (ESAL). The study employs a quantitative descriptive-correlational approach using illustrative data calibrated against real traffic parameters from the prior survey. The analysis reveals a strong negative correlation between cumulative ESAL and PCI (R² = 0.95), and a strong positive correlation between PCI and segment operating speed (R = 0.99). The segments with the highest cumulative loading, located near the convergence point with Tapian Nauli Road, showed poor condition and the most significant reduction in operating speed. This study underscores the importance of integrating structural pavement evaluation into urban traffic management studies to ensure more targeted road maintenance interventions.